Pathogen incidence and their potential as microbial control agents in IPM of maize stem borers in West Africa - Cherry, A.J.; Lomer, C.J.; Djegui, D.A.; Schulthess, F. (Springer, 1999)
A review of the existing basis for maize stem borer IPM is given and the role of pathogens in the system is evaluated. Survey work outlining the major groups of insect pathogens is described; fungi (Beauveria bassiana and Metarhizium anisopliae), bacteria (Bacillus thuringiensis and Serratia marcesens), and viruses (granuloviruses and cytoplasmic polyhedroviruses) were identified. The presence of other unidentified protozoans, nematodes, fungi and viruses was noted. The virulence of some of the more promising known insect pathogens was explored in preliminary bioassays. Considering the cryptic habits of the insects, and the low input agriculture practiced by the majority of maize farmers in sub-Saharan Africa, Beauveria bassiana isolates possessing the capacity to grow systemically in the maize plant are considered one of the more interesting candidates for development as microbial control agents despite limited control in preliminary trials. Further work should also investigate the potential of pathogens of moderate virulence, such as the protozoans and CPVs.